Reversible Image Data Hiding Using Encryption and Decryption with Contrast Enhancement - Raj, Asha S; Nair P, Mrs.Gayathri (IJRDO -Journal of Computer Science Engineering, 2016)
The Reversible Data Hiding of image Using Encryption and Decryption with Contrast Enhancement is a widely used technique. Recoverence of host image is done. Using Encryption and Decryption with Contrast Enhancement. It is applied at medical and military applications. The data embedding continous loss is inevitable. In several areas such as medical, military, and law forensics degradation of cover image is not allowed. For the sake of Reversible Image Data Hiding Using Encryption and Decryption with Contrast Enhancement. The main applications are medical and military areas. The digital images that embeds data into image. For communication seceret maintenance alteration of pixel is much needed. Reversible Image Data Hiding Using Encryption and Decryption for high security and efficiency. It enables images to data in hidden format. Restoration process is focused. The Reversible Image Data Hiding Using Encryption and Decryption with Contrast Enhancement which uses the encryption and decryption for enhancing the security of the whole system.